Shifts in Plant Chemical Defenses of Chile Pepper (Capsicum annuum L.) Due to Domestication in Mesoamerica - Luna-Ruiz, Jose de Jesus; Nabhan, Gary P.; Aguilar-Meléndez, Araceli (Frontiers in Ecology and Evolution, 2018)
We propose that comparisons of wild and domesticated Capsicum species can serve as a model system for elucidating how crop domestication influences biotic and abiotic interactions mediated by plant chemical defenses. Perhaps no set of secondary metabolites (SMs) used for plant defenses and human health have been better studied in the wild and in milpa agro-habitats than those found in Capsicum species. However very few scientific studies on SM variation have been conducted in domesticated landraces of chile peppers and their wild relatives in Mesoamerica. In particular, capsaicinoids in Capsicum fruits and on their seeds differ in the specificity of their ecological effects from broad-spectrum toxins in other members of the Solanaceae. They do so in a manner that mediates specific ecological interactions with a variety of sympatric Neotropical vertebrates, invertebrates, nurse plants and microbes. Specifically, capsaicin is a secondary metabolite (SM) in the placental tissues of the chile fruit that mediates interactions with seed dispersers such as birds, to seed predators ranging from fungi to insects and rodents. As with other Solanaceae, a wide range of SMs in Capsicum spp. function to ecologically mediate the effects of a variety of biotic and abiotic stresses on wild chile peppers in certain tropical and subtropical habitats. However, species in the genus Capsicum are the only ones found within any solanaceous genus that utilize capsaicinoids as their primary means of chemical defense. We demonstrate how exploring in tandem the evolutionary ecology and the ethnobotany of human-chile interactions can generate and test novel hypotheses with regard to how the domestication process shifts plant chemical defense strategies in a variety of tropical crops. To do so, we draw upon recent advances regarding the chemical ecology of a number of wild Capsicum species found in the Neotropics. We articulate three hypotheses regarding the ways in which incipient domestication through “balancing selection” in wild Capsicum annuum populations may have led to the release of selective biotic and abiotic pressures. We analyze which shifts under cultivation generated the emergence of Capsicum chemotypes, morphotypes and ecotypes not found in high frequencies in the wild. We hypothesize that this